Why is a very easy, useful, old technique underused? An overview of esophageal brachytherapy – interventional radiotherapy - Rovirosa, Ángeles; Tagliaferri, Luca; Chicheł, Adam; Lancellotta, Valentina; Zhang, Yaowen; Antelo, Gabriela; Hoskin, Peter; Steen-Banasik, Elzbieta van der; Biete, Albert; Kovács, György (Journal of Contemporary Brachytherapy, 2022)
Endoesophageal brachytherapy (EBT) or endoesophageal interventional radiotherapy (EIRT) is an effective technique that has been used with varying frequency for many years. It is a very good technique in T1-T2 inoperable esophageal cancer and in the palliation of dysphagia. However, only some centers have access to this technique, and consequently, it is underused. Here, we discussed the indications and several technical aspects as well as the literature available. Also, why this technique is underused and how this can be overcome. We consider that EBT is a very effective technique that should be used whenever indicated.